Estudo teórico de propriedades estruturais e elétricas de filmes automontados de moléculas orgânicas - Savedra, Ranylson Marcello Leal (Universidade Federal de São Carlos, 2014)
Compact models of ionized and nonionized Langmuir monolayers of stearic acid adsorbed on the water were simulated by means of atomistic molecular dynamics. The electrostatic, structural and dynamic properties of the molecules of models were studied throughout time evaluating the calculated trajectory. The structural analyses indicate a significant increase of the water density at the interface in comparison to the bulk aqueous phase. These results also showed that the water molecules near the interface orient hydrogen atoms toward to organic phase. The distribution of water molecules at interface neutralizes partially the charges of the polar group of stearic acid, reducing the contribution of this group of the electrostatic potential in the monolayer. The charge densities indicated two possible mechanisms of partial charges neutralization on the head of stearic acid. At low stearate concentrations, the water had the highest positive charge density contribution at the interface. However, the positive charge density is predominantly derived from monovalent ions of sodium at electrical double layer, for the monolayers with more than 30 % of the stearate in the organic phase. It was observed that water molecules at the interface have lower mobility than the bulk aqueous phase, especially those coordinating around the carbonyl group and the stearate of the organic phase.
Theoretical study of structural and electrical properties of self-assembled films of organic molecules
Keywords: Físico-química; Dinâmica molecular; Monocamada de ácido esteárico; Simulação computacional; Estrutura elétrica em interface; CIENCIAS EXATAS E DA TERRA::QUIMICA